RESEARCH ON OBTAINING HIGH Β-GLUCANS CONTENT FROM DIFFERENT SOURCES OF YEAST BY HARNESSING THEIR BIOLOGICALLY ACTIVE POTENTIAL - Ionuț AVRĂMIA (Stefan cel Mare University of Suceava, 2017)
Isolated polysaccharides from different natural sources have gained a real interest from the scientific community due to biologically active effects on body functions such as: lipid metabolism correction, immune stimulating, glycemic control in type II diabetes, antitumor activity, etc. A category of these polysaccharides is β-glucans, β-D-glucose polymers produced by various organisms such as bacteria, yeasts, algae and plants. This paper presents the experimental results obtained from the analysis of four types of yeast available on the market in order to select the one with the highest content of β-glucan, which can be later exploited in various fields: medical, pharmaceutical, food or cosmetics. According to the experimental data, the highest level of β-glucans content is represented by beer yeast, 21.49% higher than bakery yeast and 36.36% higher than wine yeast.